Evaluation of the biofilm life cycle between Candida albicans and Candida tropicalis - Atiencia-Carrera, María Belén; Cabezas-Mera, Fausto Sebastián; Vizuete, Karla; Debut, Alexis; Tejera, Eduardo; Machado, António (Frontiers in Cellular and Infection Microbiology, 2022)
Candida tropicalis is an emergent pathogen with a high rate of mortality associated with its biofilm formation. Biofilm formation has important repercussions on the public health system. However, little is still known about its biofilm life cycle. The present study analyzed the biofilm life cycle of Candida albicans and C. tropicalis during various timepoints (24, 48, 72, and 96 h) through biomass assays, colony-forming unit (CFU) counting, and epifluorescence and scanning electron microscopies. Our results showed a significant difference between C. albicans and C. tropicalis biofilms in each biomass and viability assay. All-time samples in the biomass and viability assays confirmed statistical differences between the Candida species through pairwise Wilcoxon tests (p < 0.05). C. albicans demonstrated a lower biomass growth but reached nearly the same level of C. tropicalis biomass at 96 h, while the CFU counting assays exhibited a superior number of viable cells within the C. tropicalis biofilm. Statistical differences were also found between C. albicans and C. tropicalis biofilms from 48- and 72-h microscopies, demonstrating C. tropicalis with a higher number of total cells within biofilms and C. albicans cells with a superior cell area and higher matrix production. Therefore, the present study proved the higher biofilm production of C. tropicalis.